Reconsidering counselling and consent. Issue 1 (1st December 2015) - Hall, David R.; van Niekerk, Anton A.
Abstract: In the current era patient autonomy is enormously important. However, recently there has also been some movement back to ensure that trust in the doctor's skill, knowledge and virtue is not excluded in the process. These new nuances of informed consent have been referred to by terms such as beneficent paternalism, experience‐based paternalism and we would add virtuous paternalism. The purpose of this paper is to consider the history and current problematic nature of counselling and consent. Starting with the tradition founded by Hippocrates we trace and seek to understand how relevant aspects of the patient‐doctor relationship have evolved under the influences of subsequent moral theories. Finally we tentatively endorse certain modes of counselling in the current era in order to promote morally sound, good clinical practice.